2011
DOI: 10.3390/s110505270
|View full text |Cite
|
Sign up to set email alerts
|

FT-IR-cPAS—New Photoacoustic Measurement Technique for Analysis of Hot Gases: A Case Study on VOCs

Abstract: This article describes a new photoacoustic FT-IR system capable of operating at elevated temperatures. The key hardware component is an optical-readout cantilever microphone that can work up to 200 °C. All parts in contact with the sample gas were put into a heated oven, incl. the photoacoustic cell. The sensitivity of the built photoacoustic system was tested by measuring 18 different VOCs. At 100 ppm gas concentration, the univariate signal to noise ratios (1σ, measurement time 25.5 min, at highest peak, opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Another point to consider for future improvements is that our current CEPAS detector can operate only up to 50 °C, making the handling of high-boiling-point compounds difficult as they tend to stick on the walls of the cell. However, an earlier study has shown that the CEPAS detector can operate at least up to 180 °C with suitable engineering . Overall, an optimally designed CEPAS detector could improve the detection limits of GC-PAS as much as 2–3 orders of magnitude, resulting in low-pg to sub-pg LODs and thus surpassing FID performance also in terms of detection limits, not only in selectivity.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Another point to consider for future improvements is that our current CEPAS detector can operate only up to 50 °C, making the handling of high-boiling-point compounds difficult as they tend to stick on the walls of the cell. However, an earlier study has shown that the CEPAS detector can operate at least up to 180 °C with suitable engineering . Overall, an optimally designed CEPAS detector could improve the detection limits of GC-PAS as much as 2–3 orders of magnitude, resulting in low-pg to sub-pg LODs and thus surpassing FID performance also in terms of detection limits, not only in selectivity.…”
Section: Resultsmentioning
confidence: 88%
“…However, an earlier study has shown that the CEPAS detector can operate at least up to 180 °C with suitable engineering. 43 Overall, an optimally designed CEPAS detector could improve the detection limits of GC-PAS as much as 2−3 orders of magnitude, resulting in low-pg to sub-pg LODs and thus surpassing FID performance also in terms of detection limits, not only in selectivity.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…The screw cap valve of the Tedlar bag was used for the connection to ensure sealing. This procedure for the generation of VOC gas mixtures is established among researchers in this field [ 44 ]. After the gas transfer from the preparation bag to the sample cell, the gas in- and outlet of the cell were closed.…”
Section: Methodsmentioning
confidence: 99%
“…So there will be background absorptions to a certain extent corresponding to different lters. The background PA signal corresponding to a specic lter could be considered as a xed value when the external environment conditions stay permanent, [17][18][19][20][21] because SF 6 is the major component of measured gas.…”
Section: Theoretical Derivation Of Temperature Correction Of Pa Signalmentioning
confidence: 99%